Suspended Sediment Circulation in semiclosed docks, Puerto Galvan, Argentina - Perillo, Gerardo Miguel E. (2001)
Paste one version of a text here.The circulation pattern of two docks at Puerto Galván (Bahía Blanca Estuary, Argentina) have been studied in relation to dredging operations. Even though both docks have different designs, the study shows that they are prone to import material. During the measure- ments, a fluid mud layer at the docks and in the Canal Principal was first detected in the estuary. The authors wish to thank the authorities of the Con- sorcio de Gestión del Puerto de Bahía Blanca (CGPBB) for the authorisation to use their data for the present article as well to its personnel for their support during the cruises and pre- and postprocessing of the informa- tion. Thanks go also to Mr Jurgen Nieuwenhoven and HAM Dredging for logistic support during the study.